1998
DOI: 10.1212/wnl.50.4.890
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral infarction in young adults

Abstract: In this hospital-based registry within a region characterized by racial/ethnic diversity, cardiac embolism, hematologic and other causes, and lacunar stroke were the most common etiologies of cerebral infarction in young adults. Nearly a third of both first and recurrent strokes had no identified cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
152
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(169 citation statements)
references
References 17 publications
10
152
2
5
Order By: Relevance
“…We found that younger patients were at relatively increased odds of stroke after ILI compared to older patients; for every decade younger age, the odds increased by almost 10%. While the absolute risk of stroke is greater in older adults, approximately 10–14% of all strokes occur in people 18–45 years old, with the incidence and prevalence of stroke in the young increasing 4, 28, 29, 30, 31, 32, 33, 34. This increasing prevalence, moreover, coupled with greater heterogeneity in stroke etiology within the younger age group than in the older stroke population, presents a unique and vulnerable patient population where risk reduction efforts are of increasing importance.…”
Section: Discussionmentioning
confidence: 99%
“…We found that younger patients were at relatively increased odds of stroke after ILI compared to older patients; for every decade younger age, the odds increased by almost 10%. While the absolute risk of stroke is greater in older adults, approximately 10–14% of all strokes occur in people 18–45 years old, with the incidence and prevalence of stroke in the young increasing 4, 28, 29, 30, 31, 32, 33, 34. This increasing prevalence, moreover, coupled with greater heterogeneity in stroke etiology within the younger age group than in the older stroke population, presents a unique and vulnerable patient population where risk reduction efforts are of increasing importance.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15% of all ischemic strokes (IS) occur in young adults and adolescents. [1][2][3][4][5][6][7][8] Compared with stroke in older adults, stroke in the young has a disproportionately large economic impact by leaving victims disabled before their most productive years. To date, only limited prior public health and research efforts have specifically addressed stroke in the young.…”
mentioning
confidence: 99%
“…23,41,47) Although pregnancy and the period shortly after pregnancy are widely believed to be associated with increased risk of stroke, the age-and race-adjusted relative risk (RR) is reported to be 0.7 (95% confidence interval 0.3-1.6). 23) Among 1,051,113 residents recruited in the Baltimore-Washington Cooperative Young Stroke Study, 24) 17 cerebral infarctions occurred during 8,011,852 woman-weeks of exposure, whereas 175 cerebral infarctions occurred during 101,303,016 non-exposed woman-weeks. On the other hand, the RR increased to 5.4 (95% confidence interval 2.9-10.0) during the postpartum period (after live birth or stillbirth).…”
Section: Incidence Of Ischemic Stroke During Pregnancymentioning
confidence: 99%